Practical Uses of Fruits in Ancient Medicine (based on the treatise of Quintus Gargilius Martialis Medicinae ex oleribus et pomis) - Петришин, Марта Йосипівна; Загайська, Галина Михайлівна; Любімова, Оксана Василівна (Aluna Publishing, 2024)
ABSTRACT Aim: The aimof the article is to study the therapeutic effect and pharmacological characteristics of using fruits, berries, and nuts in ancient medicine, expanding and deepening knowledge in the history of medicine. Materials and Methods: The study material was Medicinae ex oleribus et pomis, the work of Quintus Gargilius Martialis, a third-century Roman writer, a systematizer of rules for cultivating and medical application of over 60 types of vegetables and fruits. The methodological basis of the research is a set of general scientific and special research methods, including analysis and synthesis, induction and deduction, historical, interdisciplinary, descriptive methods, and the method of contextual analysis. Conclusions: Gargilius’ treatise Medicinae ex oleribus et pomis is a valuable source of knowledge about the use of vegetables, herbs, fruits, and nuts for the treatment and prevention of various diseases in antiquity. Roman physicians sought remedies in nature, considered fruit crops as a miniature pharmacy, learned to use bark, stems, flower petals, seeds, fruits, and other parts of plants to strengthen immunity, prevent and treat diseases of therapeutic and surgical profile, laying the foundations of modern phytotherapy. Ancient medicine highly valued the therapeutic and prophylactic properties of pomegranates, plums, apples, pears, quinces, figs, almonds, and other plants. Studying the experience of ancient physicians in historical retrospective, analyzing the healing properties of fruits and nuts used in their practice by ancient doctors, provides an idea of the development of the healing art, understanding the functions of the human body, means of prevention, and treatment of diseases in ancient times.
Fruits in human diet are a source not only of vitamins, organic acids, mineral salts, but also of fiber, tannins, and pectin substances, which beneficially affect di- gestion and metabolism processes, play an important role in immune system formation, health preservation, reduce the risk of gastrointestinal, cardiovascular, nervous, and circulatory system diseases, and have a beneficial effect on the human body.
Keywords: KEY WORDS: history of medicine, Quintus Gargilius Martialis, fruits, nuts, treatment, complementary alternative medicine